Trade shocks and labour market resilience in Sub-Saharan Africa: Does the franc zone response differently? - Tii Njivukuh Nchofoung (African Governance and Development Institute (AGDI), 2022)
The objective of this paper is to evaluate the impact of commodity terms of trade (CTOT) shocks on the labour market resilience of Sub-Saharan Africa (SSA) countries, comparing the franc zone countries on one hand, from the non-franc zone countries on the other hand. The results from the PVAR estimation indicate a positive impact of commodity terms of trade shocks on labour market resilience in SSA countries, a result that was replicated in both the franc zone and the non-franc zone countries. When robustness was checked through the PSTR, this positive relationship was established to be non-linear. The policy implications of the study invite the policy makers to diversify their economies to limit their heavy reliance of their economies on commodities.
Keywords: F16; F14; C23; 330; commodity terms of trade; resilience; franc zone; PVAR; PSTR